A Comparison of Simultaneous Interpretation and Delayed Simultaneous Interpretation from English into Korean - Lee, Taehyung (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis article examines real-time simultaneous interpretation (SI) and delayed SI, recorded speeches broadcast on TV through SI. The results showed that interpreters’ factors in two modes of SI had a high correlation thus showing that interpreters use a similar strategy when the speakers’ variables are identical. As expected, the quality of delayed SI was higher than that of live SI due to longer pauses, EVS and Korean sentences in live SI than those of delayed SI. Thus it was found that the quality of incoming sentences deteriorates when interpreters spend more time than allowed on a sentence. Interpreters in delayed SI, thanks to their strong sense of anticipation, produced a high quality SI by following the proper strategy. This implies that securing scripts in advance or obtaining a detailed outline by the interpreter is key to ensuring a quality SI.